Stereotactic Radiosurgery: Instrumentation and Theoretical Aspects—Part 1 - Chen, Joseph C T (The Permanente Journal, 2005)
In the five decades since its introduction as a concept, radiosurgery has been technically refined to the point where it has revolutionized many aspects of treating central nervous system disease. This article reviews the technical basis of stereotactic radiosurgery as well as the radiobiologic principles underlying its use.